2004
DOI: 10.1186/1471-2458-4-21
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to asymptomatic screening and other STD services for adolescents and young adults: focus group discussions

Abstract: BackgroundSexually transmitted diseases (STDs) are a major public health problem among young people and can lead to the spread of HIV. Previous studies have primarily addressed barriers to STD care for symptomatic patients. The purpose of our study was to identify perceptions about existing barriers to and ideal services for STDs, especially asymptomatic screening, among young people in a southeastern community.MethodsEight focus group discussions including 53 White, African American, and Latino youth (age 14–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
146
3
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(163 citation statements)
references
References 24 publications
11
146
3
3
Order By: Relevance
“…It is a 'silent infection'-70% of women and 50% of men with Chlamydia are asymptomatic (Peipert, 2003). If left untreated, Chlamydia can cause severe reproductive complications in women, such as infertility and ectopic pregnancy (Tilson et al, 2004). Chlamydia is easy to detect using a urine test and easy to treat with a single dose of antibiotics (Peipert, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a 'silent infection'-70% of women and 50% of men with Chlamydia are asymptomatic (Peipert, 2003). If left untreated, Chlamydia can cause severe reproductive complications in women, such as infertility and ectopic pregnancy (Tilson et al, 2004). Chlamydia is easy to detect using a urine test and easy to treat with a single dose of antibiotics (Peipert, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying user-friendly settings is therefore a first step in setting up any kind of screening programme (Tilson et al, 2004). Overall, however, there has been little formative research that would provide empirical findings to underpin the selection of appropriate screening settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study attempted to quantify, using a visual analogue pain scale, the discomfort associated with urethral swab collection and found that collection with a urethral swab using the standard technique (inserting a swab 2 cm into the distal urethra) elicited a median pain score of 52 mm (on a 100-mm pain scale), which correlated with moderate (Ͼ30 mm) to severe (Ͼ54 mm) pain (10). Furthermore, multiple studies have identified discomfort from urethral swabbing as a major factor that causes men to delay seeking health care (11)(12)(13), and participants in adolescent focus groups expressed strong negative emotions when asked about the urethral swab testing process (12,13). In addition, the ease of obtaining a meatal swab facilitates self-collection for NAAT, allowing patients to self-collect specimens at home or in a clinical setting where regular interval screening of asymptomatic high-risk men is performed.…”
Section: Discussionmentioning
confidence: 99%
“…While barriers to HIV testing among youth in Iran is poorly understood, decreased uptake of HIV testing among youth has been strongly associated with structural-and individual-level HIV-related stigma in numerous settings (Cunningham, Tschann, Gurvey, Fortenberry, & Ellen, 2002;Shoveller, et al, 2009;Tilson, et al, 2004).…”
Section: Discussionmentioning
confidence: 99%